Pembelajaran Tari Kreasi “Semarang Rumah Kita” pada Diaspora di Kedutaan Besar Republik Indonesia Manila-Filipina - Dyan W.W, Ade Irma; Kusumastuti, Eny (Dinasti Research, 2026)
This study aims to describe the learning process of the creative dance “Semarang Rumah Kita” at the Indonesian Embassy (KBRI) in Manila, Philippines, within the context of cultural preservation. It utilizes a descriptive qualitative approach, with data collection technique consisting of observation, interviews, and documentation. The research subjects include Indonesian diaspora students and the learning facilitators at the Education and Culture Attache of KBRI Manila. The findings indicate that the learning process is carried out through the stages of planning, implementation, and evaluation. The methods employed include demonstration, imitation, and drill. The learning process takes place within a cultural preservation framework that influences the student’s movement comprehension, and adaptation. Supporting factors include participant enthusiasm, institutional support, and adaptive nature of the dance, while inhibiting factors include time constraints and the diverse backgrounds of the students. The novelty of this study lies in the investigation of creative dance learning within a nonformal context abroad. This study contributes as a reference for the development culture-based learning strategies overseas.